Strategic Supremacy of Organizations in Dynamic Environments: An Agility Perspective - Rashid, Saleh A; Muttar, Laith Ali (South Asian Journal of Social Sciences and Humanities, 2023)
Purpose: The main purpose of the research is to highlight a new business model based on the concept of agility with its different components that enable organizations to achieve strategic supremacy in light of dynamic environments. Methodology: The research used the descriptive approach to analyze data obtained from two samples consisting of(106) heads of scientific departments, as well as (420) faculty members working at (11) private faculties in the Middle Euphrates region in Iraq . indings: The research found that achieving strategic supremacy is possible when organizations are able to ensure the required level of agility, whether at the organizational level, leadership or employees. Research implications: The research concludes that agile organizations can be more effective in a dynamic business environment and achieve strategic supremacy when they are practicing a new business model based on the perspective of agility. Originality and value: The research contributes in creating a growing interest in agility theory to help organizations deal with the continuous changes in the external environment whether it is in the education sector or other places. It also helps leaders in the surveyed faculties to identify agility competencies that still need to be developed at all levels in order to ultimately achieve strategic supremacy.